Thank you for the opportunity to help you with your question!

ok we have

y = 4(2x + 3)^5ln(2x+ 3)

dy/dx = 20(2x + 3)'(2x + 3)^4ln(2x+3) + 4(2x + 3)^5((2x + 3)'/2x + 3)

= 40(2x + 3)^4ln(2x + 3) + 4(2x + 3)^5(2/2x+3)

= 40(2x + 3)^4ln(2x + 3) + 8(2x + 3)^5/(2x+3)

= 40(2x + 3)^4ln(2x + 3) + 8(2x + 3)^4

= 8(2x + 3)^4(5ln(2x + 3) + 1)

if you don't understand just ask

Good luck

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up